Achieving a novel solvent-free regeneration of LiBH4 combining hydrogen storage and production in a closed material cycle - Kang Chen; Hao Zhong; Liuzhang Ouyang; Fen Liu; Hui Wang; Jiangwen Liu; Huaiyu Shao; Min Zhu (Journal of Magnesium and Alloys, 2023)
LiBH4 has been considered as one of the most promising energy storage materials with its ultrahigh hydrogen capacity, which can supply hydrogen through hydrolysis process or realize hydrogen-to-electricity conversion via anodic oxidation reaction of direct borohydride fuel cells (DBFCs). However, the realization of practical hydrogen applications heavily depends on the effective synthesis of high-purity LiBH4 and recycling of the spent fuels (LiBO2·xH2O). The present work demonstrates a convenient and high-efficiency solvent-free strategy for regenerating LiBH4 with a maximum yield close to 80%, by retrieving its by-products with MgH2 as a reducing agent under ambient conditions. Besides, the hydrogen released from the regeneration course can completely compensate the demand for consumed MgH2. The isotopic tracer method reveals that the hydrogen stored in LiBH4 comes from both MgH2 and coordinated water bound to LiBO2. Here, the expensive MgH2 can be substituted with the readily available and cost-effective MgH2−Mg mixtures to simplify the regeneration route. Notably, LiBH4 catalyzed by CoCl2 can stably supply hydrogen to proton exchange membrane fuel cell (PEMFC), thus powering a portable prototype vehicle. By combining hydrogen storage, production and utilization in a closed cycle, this work offers new insights into deploying boron-based hydrides for energy applications.